Malaysian audiences reaction of news frame setting towards LGBT issues - Mohd Zawawi, Julia Wirza; Hassan, Hamisah; Kho, Suet Nie; Hashim, Norliana (Global Academic Excellence, 2020)
The trending and increasing openness of news reporting has caused the media industry to shift and increasingly report news that was once considered taboo to the mass audiences. The high acceptance and rate of feedback from the readers boost the rate of coverage on taboo issues. Lesbian, Gay, Bisexual, and Transgender or commonly known as LGBT is an issue that is gaining traction on online news portals. Therefore, the main aim of this conceptual article is to discuss the effects of news presentation regarding this issue using the framing theory from three main aspects which are (i) cognitive (ii) response (attitude) and (iii) behavior (acceptance or rejection). This study can be used to shape a theoretical expectation of LGBT issues that are being presented by an online news portal today.